Geometria otimizada para a espectroscopia de Lente Térmica: aplicações em óleos vegetais e líquidos transparentes - Silva, Rubens (2010)
In this work we studied the Thermal Lens Thecnique (TLT), and we have used it as a tool in spectroscopic studies of transparent liquids. At first, we reformulated the method of determination of the waist of the laser beams. Our studies showed the need of changing of the fitting parameters of the Knife-edge Thecnique , used in the scientific works for decades. Another point of this work was a proposal of a change in the experimental setup, which was called optimized. Two kinds of optimization were approached, one without focusing the probe beam, and the other with the probe beam collimated. We explored the geometrical parameters of the experimental apparatus that influence the temporal evolution of the TL. By keeping the sample cell at the minimum waist of the excitation beam, we investigated the TL signal behaviour when the curvature radius of the probe beam and the distance between the sample and the detector were varied. Our results show that high amplitude TL signals, very close to the optimized value, combined with short transient times, may be obtained by reducing the curvature radius of the probe beam and the distance between the sample cell and the detector. In order to confirm the theoretical predictions we have measured thermal diffusivities of the following vegetable oils: olive, Brazil nut, oleic acid, palm olein and also of some transparent liquids: deionized water and ethanol. To obtain the TL signal of the transparent liquids it was necessary to use od the dyes, sunset yellow (CAC) and rhodamine B (RhB) at low concentrations.